TEACHER TALK AND CLASSROOM DISCOURSE IN INDONESIAN EFL TEACHING: AN INTERCULTURAL PERSPECTIVE - Qothrunnada, Zanuba; Rini, Setia (ELLTER Journal, 2026)
This study explores teacher talk and classroom discourse in Indonesian EFL teaching from an intercultural perspective. Using classroom discourse analysis, the study examines how teacher talk structures classroom interaction and reflects sociocultural norms embedded in instructional communication. A qualitative approach was employed, with data collected through audio-recorded classroom observations supported by field notes. The recorded interactions were transcribed verbatim and analyzed to identify interactional patterns, functions of teacher talk, and intercultural features within classroom discourse. The findings indicate that classroom interaction was predominantly teacher-initiated and largely followed the Initiation–Response–Feedback (IRF) pattern. Teacher talks primarily functioned to manage classroom activities, deliver instruction, and evaluate student responses, while opportunities for extended student participation remained limited. From an intercultural perspective, classroom discourse reflected cultural values related to respect for authority, politeness, and harmony, which influenced turn-taking practices and students’ reluctance to initiate interaction. The study highlights that teacher talk functions not only as a pedagogical tool but also as a culturally situated practice, and emphasizes the importance of reflective teacher awareness in fostering more dialogic and interculturally responsive EFL classroom discourse.